2016
DOI: 10.1037/adb0000142
|View full text |Cite
|
Sign up to set email alerts
|

Drinking group characteristics related to willingness to engage in protective behaviors with the group at nightclubs.

Abstract: Objective Electronic Music Dance Events (EMDEs) in nightclubs are settings where young adults tend to engage in high risk behaviors, such as heavy alcohol/drug use. Consequences of these behaviors may be prevented if young adults engaged in protective strategies with their drinking group. It is important to identify drinking group characteristics that predict willingness to intervene with peers. Objectives are to: 1) examine whether young adults at EMDEs would be willing to intervene with members of their drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…This ‘culture of helping’, where one's peer group offers protection against harm from others during drinking occasions , could be utilised to facilitate a safer night‐time environment. In previous research, nightclub patrons were willing to intervene with their group in order to protect them against harmful consequences of drinking . Relatedly, a behavioural analysis of aggressive incidents suggests that third‐party intervention was more likely to de‐escalate than escalate violence outcomes during conflicts recorded in public drinking spaces .…”
Section: Discussionmentioning
confidence: 99%
“…This ‘culture of helping’, where one's peer group offers protection against harm from others during drinking occasions , could be utilised to facilitate a safer night‐time environment. In previous research, nightclub patrons were willing to intervene with their group in order to protect them against harmful consequences of drinking . Relatedly, a behavioural analysis of aggressive incidents suggests that third‐party intervention was more likely to de‐escalate than escalate violence outcomes during conflicts recorded in public drinking spaces .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that individual- and group-level background variables are important for AOD use, including ethnicity (Chen & Jacobson, 2012; Khan, Cleland, Scheidell, & Berger, 2014; Miller, Byrnes, Branner, Voas, & Johnson, 2013; Shih, Miles, Tucker, Zhou, & D’Amico, 2010), gender (Khan et al, 2014), age (Chen & Jacobson, 2012; Miller, Byrnes, Branner, Johnson, & Voas, 2013), group size (Lau-Barraco, Braitman, Leonard, & Padilla, 2012), and past AOD behavior (Miller, Byrnes, Branner, Voas, & Johnson, 2013). Several of these variables have also been related to willingness to implement protective strategies with group members at nightclubs (Byrnes, Miller, Bourdeau, Johnson, & Voas, 2016). Therefore, individual control variables included gender, ethnicity, age, and past 30-day drinking/drug use at clubs.…”
Section: Methodsmentioning
confidence: 99%
“…Astudy of college students found av ariety of strategies implemented to prevent AOD-related problems among peers, such as monitoring alcohol use among the group and taking care of friends whobecome sick from AOD use (Howard et al, 2007). The fewstudies conducted among nightclub patrons found that most are willing to intervene with their peers in riskysituations (Byrnes et al, 2016).…”
Section: Peer Groups As Settings Forpreventionmentioning
confidence: 99%